Galactooligosaccharides: production, health benefits, application to foods and perspectives - Cavalcante Fai, Ana Elizabeth (2015)
Synthesized from lactose transgalactosylation, galactooligosaccharides are non-digestible carbohydrates classified as prebiotic ingredients of high added value. Recently studies associate potential health benefits and disease prevention properties to these oligosaccharides. This review involves production aspects and physicochemical properties of these compounds, correlated to their physiological effects and application in food industry. It was also presented some of the physiological effect and the perspectives for these non-conventional sugars from current viewpoint.